In-Hospital Costs Associated With an Expanded Endonasal Approach to Anterior Skull Base Tumors. (November 2022) - Parasher, Arjun K.; Lerner, David K.; Glicksman, Jordan T.; Lin, Theodore; Miranda, Stephen P.; Ebesutani, Darren; Kohanski, Michael; Lee, John Y. K.; Storm, Phillip B.; O'Malley, Bert W.; Yosher, Daniel; Palmer, James N.; et al.
Objective: To determine in-hospital costs associated with performing an EEA to anterior skull base pathology and to identify drivers of cost variability for patients undergoing endoscopic anterior skull base surgery. Methods: All endoscopic anterior skull base surgeries performed over a period from January 1st, 2015 to October 24th, 2017 were evaluated. The electronic medical record was reviewed for patient factors, tumor characteristics, and cost variables associated with each hospital stay and univariate analysis was performed using Stata software. Results: An EEA was associated with an average total in-hospital cost of 44 545. Compared to patients undergoing a transsphenoidal approach to pituitary tumor resection, EEA patients incurred higher in-hospital costs across all variables including a total cost increase of 15 921 (95% confidence interval 5720-26 122, P = .002). Univariate analysis of all endoscopic anterior skull base surgery patients showed a cost increase of 30 616 associated with post-operative cerebrospinal fluid (CSF) leak (10 420-50 811, P = .004), 14 610 with post-operative diabetes insipidus (DI) (4610-24 609, P = .004), and 11 522 with African-American patients relative to Caucasian patients (3049-19 995, P = .008). Conclusions: Patients who undergo endoscopic EEA for resection of anterior skull base tumors typically incur greater in-hospital costs than patients undergoing a standard TSA. Post-operative complications such as CSF leak and DI, as well as ethnicity, are significant drivers of cost-variability.